BEBERAPA PERMASALAHAN HUKUM PERKAWINAN DALAM KOMPILASI HUKUM ISLAM - Ba'asyien, Arsyad (State Institute of Islamic Studies (IAIN) Palu, 2007)
The protection of human rights is one the basic issues which should be paid much more attention, particularly by the state, since if it is neglected, the human’s dignity will be deteriorated. In this case, the Indonesian government has established a regulation on this issue, such as KHI (The Codification of Islamic Laws). However, among the articles of the KHI, there are also some rules, which legitimize gender inequality. Therefore, the KHI should be revised.Kata Kunci: Hukum perkawinan, Kompilasi Hukum Islam